Performance Analysis of Adaptive Noise Canceller using (NLMS) algorithm for Speech Communication Systems (Al-Mansour Journal, 2022)
Any received speech signal can be distorted by interference with an additive noise, which often can be recuperated by using special type of algorithms. In numerous wireless speech communication applications, although the speech noise characteristics are very fast , therefore, an adaptive noise canceller should be used to cancel the noise of the transmitted signal. Adaptive noise Cancellation filter is an alternative technique of estimating signals corrupted by additive noise or interference; adaptive filters such as Normalized Least Mean Squares (NLMS) algorithm have been used in a wide range of signal processing applications due to its simplicity in implementation and computation of removing the background noise and distortion.In this paper, an extensive study has been made to investigate the effects of different parameters, such as Filter length effect, step size effect , number of samples. The performance of NLMS filter for speech communication systems will be analyzed and discussed. Simulation results are presented to verify the analysis of the NLMS filter. All the results have been obtained using computer simulations built on MATLAB platform.
Keywords: Noise cancellation; Adaptive filters; Speech enhancement; NLMS filter; Signal to noise ratio (SNR); spectral analysis